Exergy Analysis of a Micro-Gas Turbine Fueled with Syngas - Sadig, Hussain (2014)
A theoretical exergetic analysis of a small-scale gas-turbine system fueled with two different syngas fuels is discussed in this paper. For carrying out the analysis, a micro-gas turbine system with a thermal heat input of 50 kW was simulated using ASPEN plus simulator. Quantitative exergy balance was applied for each component in the cycle. The effects of excess air, ambient air temperature, and heat input on the exergy destruction and exergetic efficiency for each component were evaluated and compared with those resulted from fueling the system with liquefied petroleum gas (LPG). For 50 kW heat input and 50% excess air, the total exergy destruction for LPG, Syngas1, and Syngas2 were found to be 17.3, 14.3, and 13.6 kW, respectively. It was found that increasing the excess air ratio to 100% increased the combustion chamber exergetic efficiency by 8%-10% but it reduced the exergetic efficiency of other components. The same trend was observed when tested ambient air temperature. The results also showed a reduction in the combustion chamber exergetic efficiency by 2%-4% when a 20% heat input increase was applied.